WADY WRODZONESurgical treatment of transposition of the great arteries in infants with body weight less then 2500 g - Kaźmierczak, Piotr; Moll, Jadwiga A.; Młudzik, Katarzyna; Moll, Jacek J. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Background: Low birth weight is considered as a risk factor for increased mortality in patients for early corrective surgery in cardiac defects. Arterial switch operation is the optimal operation for neonates with transposition of the great arteries. Aim: A retrospective study was undertaken to evaluate early and mid-term results of surgeries of infants with transposition of the great arteries with body weight less than 2500 g. Material and Methods: From January 2000 to December 2008, 15 patients with transposition of the great arteries underwent surgical treatment. 12 neonates underwent arterial switch operation. In 3 patients palliative procedure was performed (1 pulmonary banding and 2 Blalock-Taussig shunts). Median weight at operation was 2400 g (2070-2500 g). Results: One death after arterial switch operation and one death after pulmonary banding were observed in early postoperative period. Postoperative morbidity occurred in 75% of patients, mainly: bleeding, pneumonia and neurological deficiencies. Mild or moderate pulmonary stenosis were postoperatively observed in 2 patients. No neonates required reoperation nor invasive cardiological intervention. Conclusions: Low birth weight does not influence the survival of neonatetes with anatomically corrected transposition of the great arteries.